Pengaruh Model Pembelajaran RADEC Terhadap Pemahaman Konsep Siswa Kelas V SD Materi Sistem Pernapasan Hewan - Nina Kania Dwi; Atep Sujana; J. Julia (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aimed to examine the effect of the RADEC learning model on fifth-grade elementary school students' conceptual understanding of the animal respiratory system. Methods – This study employed a quasi-experimental method using a nonequivalent control group design. The participants consisted of 22 students assigned to the experimental group and 21 students to the control group through purposive sampling. The experimental group was taught using the RADEC learning model, whereas the control group received conventional instruction. Data were collected through observation sheets to assess the implementation of the learning process and essay tests administered as pretests and posttests to measure students' conceptual understanding. Data were analyzed using descriptive statistics, Wilcoxon Signed-Rank Test, Paired Samples t-test, Independent Samples t-test, and N-Gain analysis. Findings – The implementation of the RADEC learning model achieved a very good level of implementation 92%. Although the posttest scores of the experimental and control groups did not differ significantly sig. 0.138, the experimental group obtained a significantly higher N-Gain than the control group sig. 0.025, indicating greater improvement in conceptual understanding.Research Implications – The findings suggest that the RADEC learning model has the potential to improve elementary students' conceptual understanding. However, further studies with larger samples are needed to confirm its superiority over conventional instruction.